Knowledge, Attitudes, and Smoking Behaviours among Physicians Specializing in Public Health: A Multicentre Study. (3rd June 2014) - La Torre, Giuseppe; Saulle, Rosella; Unim, Brigid; Angelillo, Italo Francesco; Baldo, Vincenzo; Bergomi, Margherita; Cacciari, Paolo; Castaldi, Silvana; Del Corno, Giuseppe; Di Stanislao, Francesco; Panà, Augusto; Gregorio, Pasquale; et al.
Abstract : Background . Healthcare professionals have an important role to play both as advisers—influencing smoking cessation—and as role models. However, many of them continue to smoke. The aims of this study were to examine smoking prevalence, knowledge, attitudes, and behaviours among four cohorts physicians specializing in public health, according to the Global Health Profession Students Survey (GHPSS) approach. Materials and Methods . A multicentre cross-sectional study was carried out in 24 Italian schools of public health. The survey was conducted between January and April 2012 and it was carried out a census of students in the selected schools for each years of course (from first to fourth year of attendance), therefore among four cohorts of physicians specializing in Public Health (for a total of n. 459 medical doctors). The GHPSS questionnaires were self-administered via a special website which is created ad hoc for the survey. Logistic regression model was used to identify possible associations with tobacco smoking status. Hosmer-Lemeshow test was performed. The level of significance was P ≤ 0.05 . Results . A total of 388 answered the questionnaire on the website (85%), of which 81 (20.9%) declared to be smokers, 309 (79.6%) considered health professionals as behavioural models for patients, and 375 (96.6%) affirmed that health professionals have a role in giving advice or information about smoking cessation. Although 388 (89.7%) heard about smoking related issues during undergraduate courses, only 17% received specific smoking cessation training during specialization. Conclusions . The present study highlights the importance of focusing attention on smoking cessation training, given the high prevalence of smokers among physicians specializing in public health, their key role both as advisers and behavioural models, and the limited tobacco training offered in public health schools.